2016
DOI: 10.1038/srep34675
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the low-temperature metastable state in perovskite solar cells by noise spectroscopy

Abstract: The hybrid perovskite methylammonium lead iodide CH3NH3PbI3 recently revealed its potential for the manufacturing of low-cost and efficient photovoltaic cells. However, many questions remain unanswered regarding the physics of the charge carrier conduction. In this respect, it is known that two structural phase transitions, occurring at temperatures near 160 and 310 K, could profoundly change the electronic properties of the photovoltaic material, but, up to now, a clear experimental evidence has not been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 40 publications
3
22
1
Order By: Relevance
“…Recently, the low‐temperature phase transition of perovskite solar cells has been thoroughly investigated by using electric noise spectroscopy. Barone et al have shown that the dynamics of fluctuations detect the existence of a metastable state in a crossover region between the room‐temperature tetragonal and the low‐temperature orthorhombic phases of the perovskite compound, revealing the presence of a noise peak at this transition . This finding has been also confirmed by temperature dependent photoluminescence measurements reported in Figure S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…Recently, the low‐temperature phase transition of perovskite solar cells has been thoroughly investigated by using electric noise spectroscopy. Barone et al have shown that the dynamics of fluctuations detect the existence of a metastable state in a crossover region between the room‐temperature tetragonal and the low‐temperature orthorhombic phases of the perovskite compound, revealing the presence of a noise peak at this transition . This finding has been also confirmed by temperature dependent photoluminescence measurements reported in Figure S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…17 Dark noise also plays a critical role in other optoelectronic applications of hybrid organic-inorganic perovskites such as light-emitting devices, 18 photodetectors, 19 and lasers. 4 Early efforts to apply LFN characterization to perovskite materials and devices include observed increases in LFN at the tetragonal to orthorhombic phase transition in perovskites at 150 K, [20][21] probing trap energy levels in native perovskites films with LFN, 22 and correlating LFN amplitude with PCE metrics in PSCs with different interfacial layers. 23 While these preliminary reports have yielded some important insights, [20][21][22][23] LFN remains an underutilized tool to probe the electronic and ionic processes that are responsible for hysteresis and degradation in PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, electrochemical systems involving ionic interactions are studied as well. A recent report using noise studies on hybrid perovskites illustrates its utility in following the structural phase transitions as a function of temperature . Intrinsic microscopic processes such as effects from a discrete set of traps can get reflected at the macroscopic level in the form of fluctuations.…”
Section: Introductionmentioning
confidence: 99%